(untitled) (Global Journal of Human-Social Science, 2022)
Japanese schools have long provided a well-balanced education system that develops children s cognitive skills as well as their emotional and physical skills However the system has an orientation that emphasizes having children adhere to the Japanese social norms and punishes those who choose to deviate With the recent focus on Social and Emotional Learning SEL in educational research and practice will Japanese children be able to live their own lives in a 21st century society full of change and diversity This paper aims to find out how to liberate students affected by the formal education at universities the last stage of schooling Using practices at a Japanese university as a case study the paper describes how multicultural SEL creates the meaningful learning that is uniquely for their own through the students internal and external worlds and the back-and-forth between the two